2011
DOI: 10.1051/0004-6361/201116642
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamo models from direct numerical simulations and their mean-field counterparts

Abstract: Context. The test-field method permits us to compute dynamo coefficients from global, direct numerical simulations. The subsequent use of these parameters in mean-field models enables us to compare self-consistent dynamo models with their mean-field counterparts. This has been done to date for a simulation of rotating magnetoconvection and a simple benchmark dynamo, which are both (quasi-)stationary. Aims. It is shown that chaotically time-dependent dynamos in a low Rossby number regime can be appropriately de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…We also include the nonlinear generation effects which is induced by the large-scale current and the global rotation that is usually called as the Ω × J effect or the δ dynamo effect (Rädler 1969). It is supported by the numerical simulations (Käpylä et al 2008;Schrinner 2011). P08 suggested that:…”
Section: Appendixmentioning
confidence: 71%
“…We also include the nonlinear generation effects which is induced by the large-scale current and the global rotation that is usually called as the Ω × J effect or the δ dynamo effect (Rädler 1969). It is supported by the numerical simulations (Käpylä et al 2008;Schrinner 2011). P08 suggested that:…”
Section: Appendixmentioning
confidence: 71%
“…Whereas Yadav et al (2013b) obtained very similar scaling laws for models with variable conductivities, Duarte et al (2013) reported that the field topology of some models depends on the radial conductivity profile. A mean-field analysis (Schrinner et al 2007;Schrinner 2011) of numerical dynamo models in the anelastic approximation might give more detailed insight in relevant dynamo processes and is envisaged for a future study. M.…”
Section: Discussionmentioning
confidence: 99%
“…For the poloidal field, we apply a condition of smooth transition from the internal poloidal field to the external potential (vacuum) field. Summing up, the model includes magnetic field generation effects due to the differential rotation (Ω-effect), turbulent kinetic helicity (the anisotropic α-effect) and interaction of largescale currents with the global rotation, usually called Ω × Jeffect or δ-effect (Rädler 1969;Käpylä et al 2008;Schrinner 2011). For the differential rotation, we use an analytical fit to the recent helioseismology results of Howe et al (2011;see mean density and turbulent intensity gradients (so-called "gradient pumping").…”
Section: Solar Dynamo Model With Subsurface Shearmentioning
confidence: 99%